2009
DOI: 10.1007/s11738-009-0437-6
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of conditionally dormant orthodox seeds of Betula pendula

Abstract: To evaluate the feasibility of long-term cryopreservation of Polish provenances of silver birch (Betula pendula), the sensitivity of conditionally dormant seeds to extreme desiccation and/or the ultra-low temperature of liquid nitrogen (LN; -196°C) was evaluated. The critical water content (WC) of desiccated seeds and the high-moisture freezing limit of seeds desiccated or moistened to various WCs and frozen for 24 h or for 2 years in LN was also determined. Germination tests revealed no critical WC for seeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…The Canadian Forestry Service (Wang 1974) reported that B. lenta seeds tolerated desiccation to 1% MC and recommended hermetic storage at temperatures of 3°C to -25°C with 1-3% MC for their long-term conservation. Supporting the data on orthodox behavior of birch seeds, Chmielarz (2010a) reported that seeds of silver birch (Betula pendula Roth.) tolerated desiccation over silicagel to 0.02 g g -1 , with 77% of seeds germinating after 14 days of sowing.…”
Section: Discussionmentioning
confidence: 69%
“…The Canadian Forestry Service (Wang 1974) reported that B. lenta seeds tolerated desiccation to 1% MC and recommended hermetic storage at temperatures of 3°C to -25°C with 1-3% MC for their long-term conservation. Supporting the data on orthodox behavior of birch seeds, Chmielarz (2010a) reported that seeds of silver birch (Betula pendula Roth.) tolerated desiccation over silicagel to 0.02 g g -1 , with 77% of seeds germinating after 14 days of sowing.…”
Section: Discussionmentioning
confidence: 69%
“…In another study by the same researcher (Chmielarz 2009b) on mazzard cherry seeds (Prunus avium L.) it was revealed that desiccation up to an MC of 9.0-16.9% proved to be better for post-freezing regeneration (maximum of >60%) instead of deep desiccation (1.6-7.3% MC). Chmielarz (2010) reported that Betula pendula seeds could tolerate desiccation over silica gel till the level of 0.02 g g -1 (WC) and sustained germination rate of 77% after 14 days. According to that report, the optimum range of seed WC, within which the seeds tolerate the ultra-low temperature of LN was 0.02-0.23 g g -1 and further confirmed that the seeds if dehydrated properly can be stored in LN for about two years with proper after-storage germination rates.…”
Section: Influence Of Moisture Contentmentioning
confidence: 99%
“…The temperature was sustained at 23 o C and 27 o C for 22 h and 2 h per day, respectively. The use of Jacobsen germinator was also described in the reports of Chmielarz (2010) and Michalak et al (2015). As per their description, the seeds were thawed by keeping in a water bath at 40 o C for 5 min following LN exposure before transferring them in Jacobsen germinator.…”
Section: Post-cryopreservation Regrowthmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different techniques have been tested to determine the ideal storage conditions for different seeds, and therefore would require involve reducing seed metabolism usually by reducing seed water contents or lowering their storage temperatures (Kohoma et al 2006). The storage of "orthodox" seeds (such as A. coriaceae) at -18°C has been adopted by most seed banks, and this technique can prolong seed longevity for decades (Chmielarz 2010, Coelho et al 2012.…”
Section: Introductionmentioning
confidence: 99%